Diversity of monogeneans and tapeworms in cypriniform fishes across two continents - Kuchta, Roman; Řehulková, Eva; Francová, Kateřina; Scholz, Tomáš; Morand, Serge; Šimková, Andrea (International journal for parasitology, 2020)
Cypriniformes, which exhibit a wide geographical distribution, are the most species-rich group of freshwater fishes. Despite considerable research on their parasites, no reliable estimates of their parasite diversity on a large geographical scale are available. In the present review, we analyse species richness of two parasitic flatworm groups (monogeneans and tapeworms) reported from cypriniform fishes in the two most intensively studied parts of the Holarctic region, Europe and North America. We also review knowledge on parasite speciation and host-parasite coevolution, and emphasise the risk of parasite co-introduction resulting from transfers of cypriniforms among different continents. As parasite diversity in European cypriniforms has been more intensively explored, we predicted a lower level of knowledge on parasite diversity in North American fishes, despite North America having a higher diversity of cypriniforms than Europe. Our data revealed a higher mean species richness of monogeneans and tapeworms per cypriniform species in Europe compared with North America. We showed that species richness of both parasite taxa in both continents is strongly affected by sample size, but that fish traits also play an important role in determining monogenean and tapeworm species richness in European cyprinoids. We recorded higher host specificity for cypriniform parasites in North America, even within parasite genera shared by cypriniforms on both continents. The host range of monogeneans parasitising cyprinoids on both continents was affected by phylogeny, indicating an effect of parasite life history on host specificity. The difference in parasite host range between the two continents could potentially be explained by either the low overall level of sampling activity in North America or an underestimation of parasite diversity in Europe. We suggest that future research efforts be focussed on cypriniforms in order to obtain reliable data for robust assessments of parasite species richness and phylogenies, to assess host-parasite coevolution and to reveal fish biogeography.
Keywords: Animals; Severní Amerika; North America; ryby; Evropa; Fishes; nemoci ryb; Parasite diversity; Cestoda; Monogenea; Fish Diseases; Cypriniform fish; Europe; zvířata